CORRELATION OF FOVEAL AVASCULAR ZONE SIZE WITH FOVEAL MORPHOLOGY IN NORMAL EYES USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 11 (November 2015) - Samara, Wasim A.; Say, Emil A. T.; Khoo, Chloe T. L.; Higgins, Timothy P.; Magrath, George; Ferenczy, Sandor; Shields, Carol L.
Abstract : Purpose: To analyze the foveal avascular zone (FAZ) in normal eyes using optical coherence tomography angiography. Methods: Prospective noncomparative case series. The parafoveal region of 70 eyes from 67 healthy subjects was imaged using optical coherence tomography angiography to visualize the superficial and deep capillary plexuses and correlated with standard macular volume scans using spectral domain optical coherence tomography to determine foveal morphology. Results: In all 70 eyes imaged, 2 vascular plexuses could be detected within the retina: a superficial plexus within the ganglion cell layer and a deep plexus within the inner nuclear layer. A measurable FAZ was visualized in both plexuses in all imaged eyes. The FAZ area was variable in the study population with a mean of 0.266 mm 2 ± 0.097 mm 2 in the superficial plexus (range: 0.071 mm 2 –0.527 mm 2 ) and a mean of 0.495 mm 2 ± 0.227 mm 2 in the deep plexus (range: 0.160 mm 2 –0.795 mm 2 ). The FAZ area was significantly larger in the deep plexus ( P < 0.0001) compared with superficial plexus. The FAZ area in both plexuses correlated inversely with central macular thickness and central macular volume ( P < 0.0001). No significant correlation was found between superficial plexus FAZ area and age ( P = 0.55) or sex ( P = 0.34). In the same manner, no significant correlation was found between deep plexus FAZ area and age ( P = 0.13) or sex ( P = 0.13). Conclusion: Optical coherence tomography angiography provides a noninvasive method to visualize and measure the superficial and deep plexus FAZ in a normal population. The FAZ can vary in size and shape, with the FAZ area significantly larger in the deep compared with the superficial plexus. Both superficial and deep FAZ area correlate inversely with foveal thickness and volume. Abstract : Foveal avascular zone area in 70 healthy eyes measured using optical coherence tomography angiography was significantly larger at the level of the deep compared with the superficial plexus. Both had inverse correlation with foveal thickness and volume.